lncrease of Tissue Plasminogen Activator in Limbs During Venous Occlusion : A Simple Haemodynamic Model - Keber, D; Blinc, A; Fettich, J (Thrombosis and Haemostasis, 1990)
Venous occlusion of a limb is an established procedure for increasing the venous plasma concentration of tissue plasminogen activator (t-PA). In this paper a simple haemodynamic model was developed to describe the venous plasma t-PA concentration as a function of haemodynamic parameters and the local release rate of t-PA during venous occlusion of the limb. The venous plasma pool of a limb was regarded as a single well-mixed compartment with a constant input rate of t-PA. The intravascular volume, blood flow and total limb volume of the upper extremity were also measured in three healthy subjects in order to characterise the haemodynamics during venous occlusion. Venous occlusion was shown to cause such an intense decrease of blood flow through the limb that the postocclusion increase in concentration of t-PA need not be explained by an increased release rate of t-PA but could be attributed merely to the diminished dilution of the venous compartment by inflowing arterial plasma. According to our model and haemodynamic measurements, the significant differences in the postocclusion concentration of t-PA between the arrn and leg can be explained by different local release rates of t-PA.